Butylamine‐Catalyzed Synthesis of Nanocrystal Inks Enables Efficient Infrared CQD Solar Cells. Issue 45 (1st October 2018) - Kim, Junghwan; Ouellette, Olivier; Voznyy, Oleksandr; Wei, Mingyang; Choi, Jongmin; Choi, Min‐Jae; Jo, Jea Woong; Baek, Se‐Woong; Fan, James; Saidaminov, Makhsud I.; Sun, Bin; Li, Peicheng; et al.
Abstract: The best‐performing colloidal‐quantum‐dot (CQD) photovoltaic devices suffer from charge recombination within the quasi‐neutral region near the back hole‐extracting junction. Graded architectures, which provide a widened depletion region at the back junction of device, could overcome this challenge. However, since today's best materials are processed using solvents that lack orthogonality, these architectures have not yet been implemented using the best‐performing CQD solids. Here, a new CQD ink that is stable in nonpolar solvents is developed via a neutral donor ligand that functions as a phase‐transfer catalyst. This enables the realization of an efficient graded architecture that, with an engineered band‐alignment at the back junction, improves the built‐in field and charge extraction. As a result, optimized IR CQD solar cells ( E g ≈ 1.3 eV) exhibiting a power conversion efficiency (PCE) of 12.3% are reported. The strategy is applied to small‐bandgap (1 eV) IR CQDs to augment the performance of perovskite and crystalline silicon (cSi) 4‐terminal tandem solar cells. The devices show the highest PCE addition achieved using a solution‐processed active layer: a value of +5% when illuminated through a 1.58 eV bandgap perovskite front filter, providing a pathway to exceed PCEs of 23% in 4T tandem configurations with IR CQD PVs. Abstract : Phase‐transfer catalyzed colloidal‐quantum‐dot (CQD) inks are developed with the aid of a neutral donor ligand. This enables graded IR CQD solar cells exhibiting the highest power conversion efficiency (PCE) of 12.3% using large‐bandgap ( E g ≈ 1.3 eV) CQDs. By using small‐ E g (1 eV) CQDs, a new record PCE of +5.0% is demonstrated on top of a perovskite ( E g ≈ 1.58 eV) front filter.